2020
DOI: 10.1155/2020/3583989
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Ultrasound and MRI in the Mapping of Deep Pelvic Endometriosis Using the International Deep Endometriosis Analysis (IDEA) Consensus

Abstract: Objectives. The primary aim was to investigate the diagnostic accuracy of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) in the mapping of deep pelvic endometriosis (DE) in a diseased population. The secondary aim was to offer first insights into the clinical applicability of the new International Deep Endometriosis Analysis group (IDEA) consensus for sonographic evaluation, which was also adapted for MRI and surgical reporting in this study. Methods. The study was a prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 22 publications
(31 reference statements)
2
65
0
Order By: Relevance
“…This prospective study was conducted at a tertiary referral endometriosis center. It is aimed at comparing the learning curve of an ultrasound and a radiology trainee when assessing pelvic endometriosis (adenomyosis, endometriomas, frozen pelvis, and DE) in the same cohort of patients using one predefined protocol, which was based on the International Deep Endometriosis Analysis (IDEA) group consensus [ 2 ] adapted for MRI, as per Indrielle-Kelly et al [ 7 ]. Diagnostic performances of trainees were compared against the accuracy of in-house ultrasound and radiology experts and also against histologically confirmed laparoscopic findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective study was conducted at a tertiary referral endometriosis center. It is aimed at comparing the learning curve of an ultrasound and a radiology trainee when assessing pelvic endometriosis (adenomyosis, endometriomas, frozen pelvis, and DE) in the same cohort of patients using one predefined protocol, which was based on the International Deep Endometriosis Analysis (IDEA) group consensus [ 2 ] adapted for MRI, as per Indrielle-Kelly et al [ 7 ]. Diagnostic performances of trainees were compared against the accuracy of in-house ultrasound and radiology experts and also against histologically confirmed laparoscopic findings.…”
Section: Methodsmentioning
confidence: 99%
“…Both imaging modalities were reported using the ultrasound-specific protocol based on the IDEA [ 2 ] consensus. For the MRI, the protocol was adapted using some modifications [ 7 ], including removing site-specific tenderness as a soft marker and replacing sliding sign by sign of adhesions from distorted anatomy (e.g., “ear sign”). The settings and technical protocols reflected routine clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…This lack of definitive instruction makes it challenging for endometriosis surgeons to consistently practice evidence-based medicine. Knowing exactly when a transvaginal ultrasound (US) will suffice before surgery as compared to more sophisticated (and expensive) tests such as a magnetic resonance image (MRI) or barium enema is difficult to decipher ( Indrielle-Kelly et al, 2020 ). Deciding on which preoperative imaging technique to utilise requires considering the entire patient, the location and extent of disease, and previous surgical history.…”
Section: Perspectivementioning
confidence: 99%
“…5 These factors have led to a typical lengthy interval of time between symptom onset and diagnosis. 6 Despite the historical and current challenges, non-invasive imaging such as advanced transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) have demonstrated excellent diagnostic accuracy in visualising ovarian endometriomas (OE), deep endometriosis (DE) and pelvic adhesions such as pouch of Douglas obliteration 7 , which could potentially increase the likelihood of an earlier diagnosis and avoid the need for major surgery (surgical diagnosis). Besides the benefit of initiating targeted therapy for endometriosis sooner, focus groups revealed that medical labelling (i.e.…”
Section: Introductionmentioning
confidence: 99%